Chronic HIV Infection and Aging: Application of a Geroscience-Guided Approach. (1st February 2022) - Masters, Mary C.; Landay, Alan L.; Robbins, Paul D.; Tchkonia, Tamar; Kirkland, James L.; Kuchel, George A.; Niedernhofer, Laura J.; Palella, Frank J.
Abstract: The ability of virally suppressive antiretroviral therapy use to extend the life span of people with HIV (PWH) implies that the age of PWH will also increase. Among PWH, extended survival comes at a cost of earlier onset and increased rates of aging-associated comorbidities and geriatric syndromes, with persistent inflammation and immune dysregulation consequent to chronic HIV infection and to antiretroviral therapy use contributing to an overall decrease in health span. The geroscience hypothesis proposes that the root causes of most aging-related chronic diseases and conditions is the aging process itself. Hence, therapeutically targeting fundamental aging processes could have a greater impact on alleviating or delaying aging-associated comorbidities than addressing each disease individually. Extending the geroscience hypothesis to PWH, we speculate that targeting basic mechanisms of aging will improve overall health with age. Clinical features and pathophysiologic mechanisms of chronic diseases in PWH qualitatively resemble those seen in older adults without HIV. Therefore, drugs that target any of the pillars of aging, including metformin, rapamycin, and nicotinamide adenine dinucleotide precursors, may also slow the rate of onset of age-associated comorbidities and geriatric syndromes in PWH. Drugs that selectively induce apoptosis of senescent cells, termed senolytics, may also improve health span among PWH. Preliminary evidence suggests that senescent cell burden is increased in PWH, implying that senescent cells are an excellent therapeutic target for extending health span. Recently initiated clinical trials evaluating senolytics in age-related diseases offer insights into the design and potential implementation of similar trials for PWH.